Characterisation of ATP-binding cassette (ABC) transporters in bronchial epithelial cell culture models - Hutter, Victoria (2012)
In vitro epithelial cell cultures are increasingly used to model drug permeability, as predictive tools for absorption in humans. Medical regulatory agencies recommend in vitro permeability screening for biopharmaceutical classification of novel therapeutic compounds, and recently published guidelines on investigating interactions of novel therapeutic compounds with clinically relevant transporters. The expression and functionality of drug transporters in the lung is poorly characterised, and insufficient to allow detailed understanding of drug-transporter interactions in the airways. Additionally, as human in vitro permeability is used to predict absorption from rat in vivo, a rat bronchial epithelium in vitro cell line would aid the understanding of interspecies differences in transporter-mediated drug trafficking.